Valorization of Peanut Shell (Arachis hypogeae ) Composited Humic Acid as Bioadsorbent of Heavy Metal Contamination - Ninik Triayu Susparini (Jurnal Sains dan Terapan Kimia, 2025)
The problem of organic and industrial waste still be the focus problems in Indonesia, especially in the Cilegon city. In this research, organic waste and peanut shell was valorized into composite bioadsorbent for treated heavy metal contamination. The aim of this research was to create a bioadsorbent composite that is applied to adsorb heavy metals in industrial waste.The compiste bioadsorbent was used as a source of functional groups such as –COOH and -OH phenolics and –OH alcoholates that can be absorb the heavy metals. The adsorption process was carried out by mixing the bioadsorbent with the metal sample saolution for 2h. Characterization was using Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Difraction (XRD), Inductively Coupled Plasma (ICP) and Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX). Based on the experimental results, the composite bioadsorbent had macro-sized pores which were efficient in adsorbing Pb, Al, and Fe adsorption efficiencies of 66.50%, 36.16%, and 50.96% respectively. The developed composite bioadsorbent has good application prospects in sustainable environmental processing